Discordant Congenital Toxoplasmosis and Cytomegalovirus Infection in Dichorionic Diamniotic Twins. Issue 9 (7th July 2022) - Wade, Joshua; Johnson, Sarah May; Burkhardt, Ingrid; Egloff, Alexia; Thomas, Jessica; Guy, Edward; Demirjian, Alicia
Abstract : Background: Toxoplasmosis and cytomegalovirus (CMV) congenital infection present with similar clinical pictures. Both infections have long-term sequelae that can be mitigated by early detection and treatment. Coinfection is uncommonly reported. Methods: Dichorionic diamniotic twins born at 35 weeks of gestation were investigated for congenital infections due to abnormalities on the antenatal scan at 31 weeks of gestation. Antenatal investigations were delayed due to late booking and delay in maternal investigations. In the neonatal period, they suffered discordant symptoms and were both investigated for Toxoplasma gondii infection. This diagnosis was confirmed in twin 2 but proved difficult in twin 1 who had a weakly positive polymerase chain reaction with inconclusive serology. Twin 1 was also diagnosed with congenital CMV, further complicating the clinical picture. Toxoplasmosis can cause long-term sequelae, and definitive diagnosis requires serology at 12 months of age; in view of this, treatment for congenital toxoplasmosis was initiated in both twins. Twin 1 was also treated for congenital CMV. Results: Due to limitations in serological investigations in neonates, diagnosing congenital toxoplasmosis can be challenging, and initiating treatment may be warranted in suspected cases, given the risk of infective complications. Discordant presentations between twins are known in congenital toxoplasmosis and CMV, but coinfection has rarely been reported without concurrent immunocompromise. A high index of suspicion should be maintained in the twin of an infected neonate, and the possibility of multiple infections should be considered. Multidisciplinary working is crucial in reaching a diagnosis and treating appropriately.